2013
DOI: 10.1124/dmd.112.050732
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Drug-Drug Interaction Study Design: Comparison of Minimal Physiologically Based Pharmacokinetic Models on Prediction of CYP3A Inhibition by Ketoconazole

Abstract: Ketoconazole is a potent CYP3A inhibitor used to assess the contribution of CYP3A to drug clearance and quantify the increase in drug exposure due to a strong inhibitor. Physiologically based pharmacokinetic (PBPK) models have been used to evaluate treatment regimens resulting in maximal CYP3A inhibition by ketoconazole but have reached different conclusions. We compare two PBPK models of the ketoconazole-midazolam interaction, model 1 (Chien et al., 2006) and model 2 implemented in Simcyp (version 11), to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…However, there is no specification for which fold should be used and thus there is no consistency across different publications. Published articles report their predictions within 1.5-fold (Han et al, 2013), 2-fold (Chen et al, 2012), 3-fold (Gibson et al, 2009), and 5-fold (Gombar and Hall, 2013) of the observed value. It is worth mentioning here that the term "observed values" in the bottom-up approach should be distinguished from that in the top-down approach.…”
Section: Introductionmentioning
confidence: 90%
“…However, there is no specification for which fold should be used and thus there is no consistency across different publications. Published articles report their predictions within 1.5-fold (Han et al, 2013), 2-fold (Chen et al, 2012), 3-fold (Gibson et al, 2009), and 5-fold (Gombar and Hall, 2013) of the observed value. It is worth mentioning here that the term "observed values" in the bottom-up approach should be distinguished from that in the top-down approach.…”
Section: Introductionmentioning
confidence: 90%
“…Since then, investigators have been evaluating the potential options since ketoconazole was considered the strong inhibitor of choice and was used in the vast majority of DDI studies of strong CYP3A inhibition. It has been noted that both itraconazole (midazolam AUCR 6.16 – 10.8, at 200 mg once daily for 4 days) and clarithromycin (maximal midazolam AUCR 8.4 at 500 mg twice daily for 7 days) are clinically less potent than the standard high dose ketoconazole regimen (AUCR 9.5–16.7 at 400 mg once daily for 4–10 days) and are more comparable with lower dose ketoconazole (AUCR 5.2–9.2 at 200 mg once daily for 3–5 days) . That trend between itraconazole and ketoconazole is borne out in simulations using the mechanistic static model (Figure C) where a midazolam f m of 0.93 predicts an AUCR of 4.6 and 18.4 for itraconazole and ketoconazole, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this potential prolonged ketoconazole inhibition, Han et al . validated two PBPK models (Simcyp v. 11 and a custom‐built model) for their predictions of in vivo DDIs and concluded that the Simcyp v. 11 model for ketoconazole resulted in underestimation of the inhibition of intestinal metabolism, as shown for compounds like midazolam and simvastatin . In addition, Seidegard et al .…”
Section: Methodsmentioning
confidence: 99%
“…18 Based on this potential prolonged ketoconazole inhibition, Han et al validated two PBPK models (Simcyp v. 11 and a custom-built model) for their predictions of in vivo DDIs and concluded that the Simcyp v. 11 model for ketoconazole resulted in underestimation of the inhibition of intestinal metabolism, as shown for compounds like midazolam and simvastatin. 19 In addition, Seidegard et al demonstrated that 16 mg ketoconazole was capable of inhibiting intestinal metabolism without affecting the liver, and at 200 mg, ketoconazole caused complete inhibition of CYP3A4 in the intestine. 20 To simulate complete inhibition of intestinal CYP3A4 while evaluating the DDI of 400 mg q.d.…”
Section: Pbpk Modelsmentioning
confidence: 99%